KUAT TEKAN BETON DENGAN FLY ASH EX. PLTU SIJANTANG SAWAHLUNTO - Armeyn Armeyn (ITP Press)
The need of building materials increased with increasing rate of physical development. Should be attempted in the alternative building materials binder which is applied in buildings. One alternative is the binder of fly ash. Fly ash pozzolan properties and can react with lime at room temperature with an aqueous medium and form a compound that binds. This study aims to determine the influence of fly ash on compressive strength of concrete. Determination of mixture composition based on SK SNI T-15-1990-03. This study varying fly ash additive between 5%, 10%, 15%, 20% and 25% as an additive. Results of laboratory tests showed that the use of concrete with fly ash as an additive to concrete compressive strength increased from 5.195%, 1 0 .573%, 13.155%, 15.055% to 16.535% of normal concrete.